1993
DOI: 10.2307/5396
|View full text |Cite
|
Sign up to set email alerts
|

Roe Deer Survival Patterns: A Comparative Analysis of Contrasting Populations

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Animal Ecology. Summary 1. From two enclosed populations monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(43 citation statements)
references
References 63 publications
4
35
3
1
Order By: Relevance
“…Mean mortality found in our study (3.1%) and in other studies capturing wild ungulates with nets (Van Laere and Boutin 1990;Sullivan et al 1991;Boutin et al, 1993;Gaillard et al 1993;Meneguz et al 1994) are below the 4.9-8.3% mortality reported when using corral traps to capture Spanish ibex, mouflon (Ovis aries musimon) and Southern chamois (Hansen et al 1993, Marco 1995Pérez et al 1997). Our mortality data are also included within the lower range of the mortality reported for snares when capturing chamois, which ranges from 0% to 11.1% (Appolinaire et al 1984;García-González et al 1993;Berducou 1993;Struch and Baumann 2000), and for box traps, which ranges from 0% to 5.6% (Mattfeld et al 1972;Abderhalden et al 1998;Casas-Díaz 2007).…”
Section: Risk For the Animalscontrasting
confidence: 64%
See 3 more Smart Citations
“…Mean mortality found in our study (3.1%) and in other studies capturing wild ungulates with nets (Van Laere and Boutin 1990;Sullivan et al 1991;Boutin et al, 1993;Gaillard et al 1993;Meneguz et al 1994) are below the 4.9-8.3% mortality reported when using corral traps to capture Spanish ibex, mouflon (Ovis aries musimon) and Southern chamois (Hansen et al 1993, Marco 1995Pérez et al 1997). Our mortality data are also included within the lower range of the mortality reported for snares when capturing chamois, which ranges from 0% to 11.1% (Appolinaire et al 1984;García-González et al 1993;Berducou 1993;Struch and Baumann 2000), and for box traps, which ranges from 0% to 5.6% (Mattfeld et al 1972;Abderhalden et al 1998;Casas-Díaz 2007).…”
Section: Risk For the Animalscontrasting
confidence: 64%
“…Previously reported mortality for roe deer captured with drive nets ranged from 1.3% to 4.2% (Van Laere and Boutin 1990; Sullivan et al 1991;Boutin et al 1993;Gaillard et al 1993;Meneguz et al 1994). Mortality in this study (3.2%) falls in this range.…”
Section: Risk For the Animalsmentioning
confidence: 98%
See 2 more Smart Citations
“…We found no overall difference between yearling and adult survival. Gaillard et al (1993) found that the survival of ''juvenile'' roe deer was more sensitive to external influences compared to adult survival. We do find this difference in the model with the lowest deviance from the data, but this effect was not significant.…”
Section: Age Effectsmentioning
confidence: 97%